Preoperative Frailty Assessment and Outcomes At 6 Months or Later In Older Adults Undergoing Cardiac Surgical Procedures: A Systematic Review - Kim, Dae Hyun (Ann Intern Med, 2016)
BACKGROUND: Frailty assessment may inform surgical risk and prognosis that are not captured by conventional surgical risk scores. PURPOSE: To evaluate the evidence for various frailty instruments to predict mortality, functional status, or major adverse cardiovascular and cerebrovascular events (MACCE) in older adults undergoing cardiac surgical procedures. DATA SOURCES: MEDLINE and EMBASE (without language restrictions), from their inception to May 2, 2016. STUDY SELECTION: Cohort studies that evaluated the association of frailty with mortality or functional status at ≥6 months in patients aged ≥60 years undergoing major or minimally invasive cardiac surgical procedures. DATA EXTRACTION: Two reviewers independently extracted study data and assessed study quality. DATA SYNTHESIS: Mobility, disability, and nutrition were frequently assessed domains of frailty in both types of procedures. In patients undergoing major procedures (N=18388, 8 studies), 9 frailty instruments were evaluated. There was moderate-quality evidence to assess mobility or disability and very-low-to-low-quality evidence to use a multi-component instrument to predict mortality or MACCE. No studies examined functional status. In patients undergoing minimally invasive procedures (N=5177, 17 studies), 13 frailty instruments were evaluated. There was moderate-to-high-quality evidence to assess mobility to predict mortality or functional status. Several multi-component instruments predicted mortality, functional status, or MACCE, but the quality of evidence was low to moderate. Multi-component instruments that measure different frailty domains seemed to outperform single-component instruments. LIMITATIONS: Heterogeneity of frailty assessment, limited generalizability of multi-component frailty instruments, few validated frailty instruments, and potential publication bias. CONCLUSIONS: Frailty status, assessed by mobility, disability, and nutritional status, can predict mortality at 6 months or later after major cardiac surgical procedures and functional decline after minimally invasive cardiac surgical procedures. PRIMARY FUNDING SOURCE: National Institute on Aging and National Heart, Lung, and Blood Institute; there was no registration for this review.